German Constitutional Law Introduction, Cases, and Principles - Bumke, Christian 1963- (Oxford University Press, Incorporated, 2019)
This revised English translation of the 7th edition of the Casebook Verfassungsrecht includes an outline of the German constitution, the BVerfG Court, and its jurisprudence. It condenses more than six decades of constitutional jurisprudence in order to familiarize readers with the style, technique, and language of the Court